Novel probiotics adsorbing and excreting microplastics in vivo show potential gut health benefits - Teng, Xin; Zhang, Tengxun; Rao, Chitong (Frontiers in Microbiology, 2025)
Microplastics (MP) contamination in food and water poses significant health risks. While microbes that form biofilm show potential for removing MP from the environment, no methods currently exist to eliminate these non-degradable MP from the human body. In this study, we propose using probiotics to adsorb and remove ingested MP within the gut. We conducted a comprehensive evaluation of 784 bacterial strains to assess their ability to adsorb 0.1 μm polystyrene particles using a high-throughput screening method. Among the tested strains, Lacticaseibacillus paracasei DT66 and Lactiplantibacillus plantarum DT88 exhibited optimal adsorption in vitro and were effective across various MP types. In an animal model, mice treated with these probiotics demonstrated a 34% increase in PS excretion rates and a 67% reduction in residual polystyrene (PS) particles within the intestine. Additionally, administration of Lactiplantibacillus plantarum DT88 mitigated PS-induced intestinal inflammation. Together, our findings demonstrate a novel probiotic strategy for addressing MP-associated health risks, emphasizing the potential of strain-specific probiotics to remove MP from the gut environment.